2021
DOI: 10.53318/msp.v11i1.1886
|View full text |Cite
|
Sign up to set email alerts
|

Connaissances et attitudes des parents face a la contraception des adolescentes a Yirimadio, Bamako

Abstract: Introduction : L’adolescence est une période de transition entre l’enfance et l’âge adulte, au cours de laquelle l’individu acquiert la plénitude de ses fonctions de reproduction où survient une sexualité précoce avec des conséquences comme les grossesses non désirées. L’objectif était d’étudier les déterminants qui influent sur les connaissances et attitudes des parents face à l’utilisation des services de planification familiale (PF) par les adolescentes dans l’aire de santé de Yirimadio. Matériel et méthode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This confirms that fixed prosthesis is reserved for those with better economic situations, as previous studies have reported [9,10]. Diallo K et al reported the same result in their study [7].…”
Section: Socio-professional Profile (Table I)supporting
confidence: 88%
See 2 more Smart Citations
“…This confirms that fixed prosthesis is reserved for those with better economic situations, as previous studies have reported [9,10]. Diallo K et al reported the same result in their study [7].…”
Section: Socio-professional Profile (Table I)supporting
confidence: 88%
“…Forty-three (43) cases of loosening were observed over a 5-year period. This loss of retention was the most common reason for consultation with 64.29% of cases in Mali [7] and was considered the most frequent failure among technical complications according to Benhamou W [2].…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…633 So far, the last Tuareg insurgency broke out in 2012. 634 After the Arab Spring and the fall of Gaddafi, about 3,000 former mercenaries returning from Libya joined the rebel groups. 635 It was not a surprise that the already weak Malian government was not capable of handling the situation, and the frustrated military led a coup to topple then President Amadou Toumani Touré.…”
Section: Vi11 Backgroundmentioning
confidence: 99%